Analisis Kinerja Karyawan Divisi Marketing PT. Graha Medika Mandiri - Talitha Amalia Charisma; Sulastri Irbayuni (Universitas Batanghari, 2022)
This study aims to analyze the performance of employees in the marketing division of PT Graha Medika Mandiri through the influence of workload and work discipline. As a distributor of laboratory equipment & tools in the South Kalimantan region, meeting work targets often results in excessive anxiety and fatigue due to the high workload. This has an impact on individual negligence in managing attitudes and responsibilities, resulting in the level of work discipline. The research methodology is quantitative through analysis of the SEM data model and the SmartPLS software approach. The sampling technique used was saturated sampling, with a total sample of 48 respondents. The findings in the study indicate that the high level of workload received, can reduce the resulting performance. Meanwhile, the level of awareness of individual work discipline can also improve employee performance. A balanced distribution of workloads is able to improve the quality of individual work through maximum and significant work discipline to produce optimal performance. This can be used as material for future evaluations for the management in determining the standardization of a balanced workload for the achievement of company goals.